2009
DOI: 10.1097/ta.0b013e3181ae6f1c
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography as a Better Indicator of Hypercoagulable State After Injury Than Prothrombin Time or Activated Partial Thromboplastin Time

Abstract: Objectives To investigate the hemostatic status of critically ill, nonbleeding trauma patients. We hypothesized that a hypercoagulable state exists in patients early after severe injury and that the pattern of clotting and fibrinolysis are similar between burned and nonburn trauma patients. Materials and Methods Patients admitted to the surgical or burn intensive care unit within 24 hours after injury were enrolled. Blood samples were drawn on days 0 through 7. Laboratory tests included prothrombin time (PT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
233
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(249 citation statements)
references
References 57 publications
9
233
1
4
Order By: Relevance
“…TEG analysis has also been shown to be a better indicator of hemostasis than PT (20,23). Recently, Zaar et al (37) demonstrated a reduction in time to fibrin formation after LBNP to presyncope demonstrated by shortened R-time.…”
Section: Discussionmentioning
confidence: 99%
“…TEG analysis has also been shown to be a better indicator of hemostasis than PT (20,23). Recently, Zaar et al (37) demonstrated a reduction in time to fibrin formation after LBNP to presyncope demonstrated by shortened R-time.…”
Section: Discussionmentioning
confidence: 99%
“…In burn patients, Park et al (24) reported that only thrombelastography analysis of whole blood revealed that patients were in a hypercoagulable state. Like in our experiment, hypercoagulability was not detectable by plasma-based clotting assays (PT and aPTT).…”
Section: Discussionmentioning
confidence: 99%
“…[19] However, with increasing tissue trauma, the progressively increasing catecholamine level further enhances thrombin generation, which exceeds the released level of tPA and PC; the net hemostatic effect is hypercoagulability. [19,20] This pathway may underlie the changes in coagulation function in group 3. In group 4, both R time and K time were signifi cantly prolonged compared with those of the other groups, and MA significantly decreased.…”
Section: Discussionmentioning
confidence: 99%